2020
DOI: 10.1038/s41598-020-65266-9
|View full text |Cite
|
Sign up to set email alerts
|

A mesophotic black coral forest in the Adriatic Sea

Abstract: A forest of the black coral Antipathella subpinnata was found from 52 to 80 m depth in three different sites at Tremiti Islands Marine Protected Area (MPA; Mediterranean Sea), with two of them hosting a monospecific forest on horizontal and vertical substrates. Colonies of A. subpinnata showed a mean density between 0.22 ± 0.03 and 2.40 ± 0.26 colonies m −2 (maximum local values of 2.4-7.2 colonies m −2). The link between the local distribution of A. subpinnata and the main oceanographic features confirmed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 40 publications
1
48
0
Order By: Relevance
“…highlighting as marine litter represents one of the major pollution problems harming benthic organisms and habitats (Gilman, 2015). These methods do not cause any impact to the marine environment and are thus applicable in protected and sensitive areas such as marine protected areas (MPAs) and coral reefs (e.g., Betti et al, 2019Betti et al, , 2020Chimienti et al, 2020). From videos and frame/photo, it is possible to obtain high-resolution quantitative data (depending on optical device), precise geolocalization, and provides in situ information at various depths.…”
Section: Methods Used To Detect Impactsmentioning
confidence: 99%
See 3 more Smart Citations
“…highlighting as marine litter represents one of the major pollution problems harming benthic organisms and habitats (Gilman, 2015). These methods do not cause any impact to the marine environment and are thus applicable in protected and sensitive areas such as marine protected areas (MPAs) and coral reefs (e.g., Betti et al, 2019Betti et al, , 2020Chimienti et al, 2020). From videos and frame/photo, it is possible to obtain high-resolution quantitative data (depending on optical device), precise geolocalization, and provides in situ information at various depths.…”
Section: Methods Used To Detect Impactsmentioning
confidence: 99%
“…They recovered with an Agassiz trawl some fragments of a Desmophyllum pertusum colony growing on a nylon net cords at 752-864 m depth in the Blanes Canyon (Western Mediterranean Sea). Chimienti et al (2020) observed a steel cable directly within a group of Antipathella subpinnata colonies in the Tremiti Islands MPA. Angiolillo and Canese (2018) observed fishing lines fully incorporated in the yellow scleractinian Dendrophyllia cornigera on the Mantice Shoal in the Ligurian Sea.…”
Section: Other Interactions (Substratum and Incorporation)mentioning
confidence: 99%
See 2 more Smart Citations
“…Antipathella subpinnata commonly lives in mixed assemblages with arborescent gorgonian octocorals, such as Paramuricea clavata (Risso, 1826) ( Enrichetti, 2019 ; Chimienti et al, 2020 ) and Eunicella cavolini (Koch, 1887) ( Bo et al, 2009 ; Gori et al, 2017 ), which are commonly found at shallow and mesophotic depths. While it is unknown how these black corals and gorgonians interact, the similar colony structures and polyps sizes ( Weinberg, 1976 ; Bo et al, 2018 ) suggest that they may occupy the same trophic niche.…”
Section: Introductionmentioning
confidence: 99%